A prehistoric copper-production centre in central Thailand: its dating and wider implications. (August 2020) - Higham, Thomas F.G.; Weiss, Andrew D.; Higham, Charles F.W.; Ramsey, Christopher Bronk; d'Alpoim Guedes, Jade; Hanson, Sydney; Weber, Steven A.; Rispoli, Fiorella; Ciarla, Roberto; Pryce, Thomas O.; Pigott, Vincent C.
Abstract: Abstract : The Khao Wong Prachan Valley of central Thailand is one of four known prehistoric loci of copper mining, smelting and casting in Southeast Asia. Many radiocarbon determinations from bronze-consumption sites in north-east Thailand date the earliest copper-base metallurgy there in the late second millennium BC. By applying kernel density estimation analysis to approximately 100 new AMS radiocarbon dates, the authors conclude that the valley's first Neolithic millet farmers had settled there by c . 2000 BC, and initial copper mining and rudimentary smelting began in the late second millennium BC. This overlaps with the established dates for Southeast Asian metal-consumption sites, and provides an important new insight into the development of metallurgy in central Thailand and beyond.